Carriage of ESBL-producing Enterobacteriaceae in French hospitals: the PORTABLSE study. Issue 3 (March 2018) - Pilmis, B.; Cattoir, V.; Lecointe, D.; Limelette, A.; Grall, I.; Mizrahi, A.; Marcade, G.; Poilane, I.; Guillard, T.; Bourgeois Nicolaos, N.; Zahar, J-R.; Le Monnier, A.
Summary: Background: Currently, contact precautions are recommended for patients colonized or infected with extended-spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-PE). Recent studies have challenged this strategy. This study aimed to assess the rate of ESBL-PE faecal carriage among hospitalized patients according to type of hospital ward, and to identify risk factors associated with carriage. Methods: A point prevalence study was conducted in five different types of hospital ward [medical, surgical, intensive care unit (ICU), after care and rehabilitation, and geriatric] in eight French hospitals. All patients included in the study provided a fresh stool sample. Results: In total, 554 patients were included in the study, with a median age of 73 years (range 60–82 years). The overall faecal carriage rate of ESBL-PE was 17.7%. The most frequently encountered species among ESBL-PE was Escherichia coli (71.4%), followed by Klebsiella pneumoniae (14.3%). Risk factors associated with ESBL-PE faecal carriage on univariate analysis were: living in the Paris region ( P <0.01) and hospitalization on a geriatric ward ( P <0.01). Interestingly, the cumulative duration of hospital stay before screening was not associated with a significantly higher prevalence of ESBL-PE carriage, regardless of ward type. The ESBL-PE colonization rate was much higher for patients hospitalized on geriatric wards (28.1%) and ICUs (21.7%) compared with those for patients hospitalized on surgical wards (14.8%), medical wards (12.8%) or aftercare and rehabilitation (11.2%). Conclusion: The overall prevalence of ESBL-PE faecal carriage was 17.7%, with only 21% of patients identified previously as carriers. The delay between admission and screening was not associated with an increase in ESBL-PE faecal carriage.